Pengaruh Dana Perimbangan dan Investasi terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Atmini Lara Santi; Hardiani Hardiani; Rosmeli Rosmeli (Jurnal Ekonomi Aktual, 2021)
This study aims to analyze the effect of fiscal balance funding and investment on economic growth in Jambi Province. The data used is time-series data from 2002-2018. The data is sourced from the Central Statistics Agency of Jambi Province and the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia. Data were analyzed by multiple regression analysis. The study results show that, either simultaneously or partially, Profit Sharing Funds, General Allocation Funds, Special Allocation Funds, Foreign Investments, and Domestic Investments have a significant influence on economic growth in Jambi Province.